LEXICO PHRASEOLOGICAL LACUNAS IN THE ENGLISH LANGUAGE - Boranbaeva Shakhsanem Kdırbaevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: This article explores the types and proper use of lacunas in English language. Article begins by defining linguacultural analysis and its key elements including the examples of the languages in various contexts in which they were used. It also provides a comprehensive overview of previous research in the English language. The ways of applying lacunas and connotations and contextualizing of them are also provided .Overall, this study highlights the importance of lacunar units in fictional literary works.